2017
DOI: 10.24093/awej/vol8no4.29
|View full text |Cite
|
Sign up to set email alerts
|

Using Infographics in the Teaching of Linguistics

Abstract: Information graphics (infographics) are visualizations of ideas & information in a type of picture. Infographics combine data with design in order to communicate information to an audience in a comprehensible manner. This study is motivated by the lack of resources that directly study the influence of infographics on linguistics. It aims to investigate the impact of using information graphics in the teaching of linguistics on Saudi students. The researchers seek to answer the following questions: (i)

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Using infographics in a language classroom is lauded as a method that enhances learning (Dahmash, Al-Hamid, & Alrajhi, 2017). Several studies have found that using infographics and related materials may considerably enhance students' learning experiences, even if they are not as commonly utilized as other mediums like PowerPoint or Word documents.…”
Section: Using Infographics In Writing Classesmentioning
confidence: 99%
“…Using infographics in a language classroom is lauded as a method that enhances learning (Dahmash, Al-Hamid, & Alrajhi, 2017). Several studies have found that using infographics and related materials may considerably enhance students' learning experiences, even if they are not as commonly utilized as other mediums like PowerPoint or Word documents.…”
Section: Using Infographics In Writing Classesmentioning
confidence: 99%